Optimization on machining parameters of friction surfacing of SS304 over iron plate. (2020) - Sakthivelu, S.; Sethusundaram, P.P.; Selwin, M.; Meignanamoorthy, M.; Dinesh Kumar, S.; Alagarsamy, S.V.
Abstract: Surface engineering deals with the surface of the material and it was sub-discipline of materials science. Wear can be reduced by modifying the surface properties of solids by coating hard material or by use of lubricants. Friction surfacing is one of the surface coating method which gives better bonding on plane surfaces. In this work, iron plate was taken as substrate and stainless steel (SS) 304 was used as coating material. The experiment was conducted based on L9 orthogonal array. The parameters chosen for the experiment were rotational speed, axial load and traverse speed. The response values were hardness and maximum displacement in order to improve the wear, corrosion and bonding strength. The results were analyzed using Taguchi method to find the optimum machining parameters and to identify the effect of machining parameter for maximum hardness and displacement. ANOVA was employed to confirm the result obtained from Taguchi method. ANOVA was also used to identify the contribution percentage of each parameters.